Research into the Influence of Swirling Wood Grain on Wood Splintering at Milling Finger Joint Elements (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The object of the study is the influence of swirling wood grain on wood splintering at milling finger joint elements. The study was carried out on the example of jointed cladding slats made of larch wood, used for the exterior finishing of the entrance group of a building.To conduct the study, photographs were taken of the slat joint areas that exhibit defects in tenoning operation (wood splintering) and, for comparison, those without such defects were used. The photographs were imported into the CAD, where the angle of annual growth ring deviation was measured. Subsequently, a statistical analysis of the measurement results was carried out. Processing of the measurement results using the least squares method made it possible to obtain the regression dependence of the probability of wood splintering on the angle of annual growth ring deviation near a knot.
Keywords: finger joint; tenoning; knot; annual ring; angle; splintering; probability; regression dependence